206k views
5 votes
Solve By elimination PLEASE=> 3x+2y=-26\ 4x-5y=-4

2 Answers

2 votes

3x + 2y = -26

4x - 5y = -4

To eliminate, we are going to cancel out the y

So multiply the first equation by 2.5, and you'll get

7.5x + 5y = -65

Add this equation to the second, and you'll get

11.5x = -69

Divide by 11.5 on both sides, and you get

x = -6

Now plug the -6 into the first equation, and you get

3(-6) + 2y = -26

Solve

-18 + 2y = -26

2y = -8

y = -4

User Tool
by
6.4k points
6 votes

Answer:x=-6 y=-4

Explanation:

User Tlcowling
by
5.7k points